Renewing Christian worldview : a holistic approach for spirit-filled Christians - Felix-Jager, Steven; Shin, Yoon (Grand Rapids, MI. Baker Academic, 2023)
"This book offers a brief but comprehensive introduction to Christian worldview from a Pentecostal perspective, helping students understand why Christianity is beautiful, true, and relevant to all aspects of life"--
Includes bibliographical references and indexes.
Keywords: Pentecostalism; Christianity -- Philosophy; Aesthetics -- Religious aspects -- Pentecostal churches; Religious ethics; Knowledge, Theory of